Special aspects of coordination ability development of 7-8 year-old acrobatic rock'n'roll athletes - Nataliya Batieieva; Petro Kyzim (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to determine the dynamics of development of coordination abilities of 7-8 years old acrobatic rock-and-roll athletes. Material & Methods: following research methods were used: theoretical analysis and generalization of data from special scientific and methodological literature; pedagogical observation; pedagogical testing; methods of mathematical statistics. Results: results of a pedagogical study of the development of the coordination abilities of 7-8 years old acrobatic rock-and-roll athletes indicate a significant increase in the indicators of coordination abilities, which confirm that the use of special exercises is an effective approach in the training process. Conclusion: comparison of the dynamics of statistical indicators of final testing of acrobatic rock'n'roll athletes showed an increase in all tested indicators.